HEADACHE SYNDROME IN ADOLESCENTS WITH AUTONOMIC DYSFUNCTION (VEGETATIVE DYSTONIA) SYNDROME (International journal of medical sciences, 2025)
The structure of headache in adolescents with autonomic dysfunction (vegetative dystonia) syndrome is presented, including types, clinical characteristics, associated manifestations, and relationships with other factors. A total of 167 respondents aged 12 to 18 years were observed. The patients had no significant organic neurological or somatic disorders and were not under specialist follow-up. Among the examined individuals, the majority experienced headaches at least once a month or more often, but only 53.3% reported them, which indicates the subjective perception of this condition and adds additional complexity to its analysis and evaluation. Mental load, stress, and physical exertion were identified as headache triggers. In studying the headache syndrome in adolescents with autonomic dysfunction, gender differences were determined.